Empirical-Scientific Model of Geography - Chojnicki, Zbyszko (Quaestiones Geographicae, 2011)
The article presents a philosophical-methodological conception of an empirical-scientific model of geography as an empirical science. It consists of an introduction and two parts. The introduction discusses the notion of philosophical-methodological models of geography and philosophical orientations. Part one addresses the philosophical-methodological foundations of the model, which are three successive philosophical streams: empiricism, logical empiricism (neo-positivism), and scientific philosophy. Part two offers a characterisation of the empirical-scientific model in terms of the principles of scientific philosophy embracing three chief problem areas: ontological, epistemological and methodological.